Development Of Aquaponic System Using Solar Powered Control Pump - Najmiah Radiah, Mohamad; A.S.A.M, Soh; Azahari, Salleh; Nik Mohd Zarifie, Hashim; Mohamad Zoinol Abidin, Abd Aziz; Nuraishah, Sarimin; Adib, Othman; Z.A, Ghani (International Organization Of Scientific Research (IOSR), 2013)
This paper describes the development of an aquaponic system using solar panel to control the water pump and air pump based on Peripheral Interface Controller (PIC) technology. Solar power is ideally can be used in Malaysia due to location factor and also give the benefit to the environment as renewable energy. It involves a combination of electrical, electronics and agriculture into one sustainable system which consists of a solar panel, inverter, water pump and air pump. The solar panel is the most cleanest ways to produce electricity. With the average output voltage is 12V while the maximum output voltage produce by the solar panel is 18 V. The voltage depends on light capture by solar panel. Weather can minimize the light capture by solar panel thus affect the overall performance. This project requires a substitution power grid with green energy from solar panel which an inverter is used to convert Direct Current (DC) to Alternate Current (AC) and to step up 12V to 110V or 240V. A microcontroller is used to control the operation of an aquaponic system for switching water pump, air pump, battery charge and discharge state. Based on observation, the output power from inverter has produced 65.55% efficiency and the average output voltage of the solar panel is 16.16 V.